The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s13197-018-3078-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of composition and storage time on some physico-chemical and rheological properties of probiotic soy-cheese spread

Abstract: Probiotic soy-cheese spread was prepared by fermenting soymilk with specific probiotic starter culture, and there after processing the coagulated mass. Soy cheese spread samples had more than 10 cfu/g of viable probiotic count at the time of preparation; and had around 17.6% protein, 25.3% fat and 19.8% total soluble sugar. Compared to commercially available dairy cheese spread, probiotic soy cheese spread had significantly higher protein and anti-oxidant activity. Soy cheese spreads, prepared from pure soymil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…The trends of G′ and G′′ were similar to other studies [ 34 , 57 ]. The G′ in Feta-type cheese made from MCC-6 was the highest, followed by Feta-type cheese made from milk and MCC-3, while the lowest G′ was noticed in Feta-type cheese made from MCC-9.…”
Section: Resultssupporting
confidence: 90%
“…The trends of G′ and G′′ were similar to other studies [ 34 , 57 ]. The G′ in Feta-type cheese made from MCC-6 was the highest, followed by Feta-type cheese made from milk and MCC-3, while the lowest G′ was noticed in Feta-type cheese made from MCC-9.…”
Section: Resultssupporting
confidence: 90%
“…After cheese manufacture, the pH values of cheeses were measured between 4.77-5.30. were determined approximately 1.5-2 times that of cheese manufacture from cow's milk only. Giri, Tripathi, & Kotwaliwale (2018) showed that the bioactivity of cheese produced with soy drink was 1…”
Section: Resultsmentioning
confidence: 99%
“…After cheese manufacture, the pH values of cheeses were measured between 4.77-5.30. Giri, Tripathi, & Kotwaliwale (2018) values due to some differences in our raw materials and cheese production conditions. Filho, Hirozawa, Prudencio, Ida, & Garcia (2014) examined the antioxidant activities of petit-suisse and quark cheeses produced from black soybeans.…”
Section: Resultsmentioning
confidence: 99%
“…The textural properties of cheese where milk fat was substituted in whole or in part with vegetable oil were investigated by Yu and Hammond [20], Lobato-Calleros et al [21], Cunha et al [22], Arslan et al [23], Abd El-Salam [24], Al-Ismail et al [25], Felfoul et al [26], Hjalmarsson [27], Badem and Uçar [28], Yagoub et al [29] and Abd El-Wahed and Hassanien [30]. The rheological properties of cheese were discussed by Lee et al [31], Budiman et al [32], Liu et al [33], Sadowska et al [34], Oliveira et al [35], Sołowiej [36], Cunha et al [37], Farbod et al [38], Hanáková et al [39], Karaman et al [40], Henno et al [41], Rafiq and Ghosh [42], and Giri et al [43]. Changes in the viscoelastic properties of cheese were also evaluated during ripening.…”
Section: Introductionmentioning
confidence: 99%